Glicerina associada ï¿½ ureia na terminaï¿½ï¿½o de bovinos: Parï¿½metros ruminais, digestibilidade e massa microbiana - D'Aurea, A. P. [UNESP]; Ezequiel, J. M.B. [UNESP]; D'Aurea, E. M.O. [UNESP]; Fï¿½varo, V. R. [UNESP]; Homem Jï¿½nior, A. C. [UNESP]; Van Cleef, E. H.C.B. [UNESP]; Paschoaloto, J. R. [UNESP]; Almeida, M. T.C. [UNESP] (FapUNIFESP (SciELO), 2017)
The aim of this research was to investigate the combination of glycerol with urea as the ruminal parameters, digestibility and quality of microbial mass. The work was conducted at the Animal Unit of Digestive and Metabolic Studies belonging to the Faculty of Agricultural Sciences and Veterinarias-FCAV/Unesp campus Jaboticabal. Six animals fitted with rumen cannulas Nellore were used to verify the parameters pH, ammonia nitrogen, digestibility, and microbial mass distributed in a 6x6 Latin square. Six diets with similar metabolizable energy and crude protein were formulated using the forage:concentrate ratio of 30:70. The roughage used was corn silage. The concentrates used were composed of corn, soybean hulls, sunflower meal, glycerin and urea. The treatments were: C = control, U = 1 [%] urea, G10 = 10 [%] glycerin, GU10 = 1 [%] urea and 10 [%] glycerol, G20 = 20 [%] glycerin and GU20 = 20 [%] glycerin and 1 [%] urea. Diets with glycerin had lower digestibility of NDF and hemicellulose. There was no influence of diets on the growth of rumen microorganisms, pH and ammonia nitrogen. Diets with 20 [%] glycerin in the diet dry matter decrease the population of rumen protozoa. The addition of glycerol decreases the digestibility of fibrous components of the diet.
Glycerin associated with urea in finishing cattle: Ruminal fermentation, digestibility and microbial mass